Genome–Wide Investigation of the CBL–CIPK Gene Family in Oil Persimmon: Evolution, Function and Expression Analysis during Development and Stress - Cuiyu Liu; Yanpeng Wang; Jin Yao; Xu Yang; Kaiyun Wu; Guoxin Teng; Bangchu Gong; Yang Xu (Horticulturae, 2022)
Ca2+-sensors, calcineurin B-like proteins (CBLs), and calcineurin B-like protein-interacting protein kinases (CIPKs) form a CBL–CIPK complex to regulate signal transduction. This study aimed to reveal the characteristics of the CBL–CIPK gene family in oil persimmon (Diospyros oleifera). Ten DoCBL and 23 DoCIPK genes were identified, and gene duplication among them was mainly attributed to segmental duplication. According to phylogenetic and structural analysis, DoCBLs were clustered into four groups with distinct motifs, namely myristoylation and palmytoylation sites in their N-terminus, and DoCIPKs containing a NAF/FISL domain were clustered into intron-rich and intron-less groups. The expression patterns of DoCBLs and DoCIPKs were tissue- and time-specific in different tissues and at different stages of fruit development. Most CBL–CIPK genes were upregulated under NaCl, drought, and Ca(NO3)2 stress using qRT-PCR analysis. DoCBL5 and DoCIPK05 were both located in the plasma membrane of cells using green fusion proteins (GFP) in tobacco leaves. DoCBL5 and DoCIPK05 might interact with AKT1, PP2C, and SNF to regulate the Ca2+ signals, K+, and ABA homeostasis in cells. In conclusion, these results suggested that the CBL–CIPK family genes might play important roles in oil persimmon growth and stress responses.